Farming practices and breeding objectives identification of farmer in north shoa and south wello zones of Amhara region - Belayhun, Teklewold; Getachew, Tesfaye; Mustefa, Amine; Engdawork, Aweke; Sinke, Seble; Melesse, Aberra (Elsevier, 2023)
The study aims at assessing the production systems and identifying the traits preferred by farmers in the study areas to establish community-based breeding and sustainable utilization programs. The study was conducted in the four purposively selected districts of North Shoa and South Wello zones of Amhara region (Merehabete, Wereillu, Moretena Jiru and Mojaena Wedera). A total of 120(30 farmers from each district) purposively selected farmers participated in their own flock ranking experiment. Furthermore, 216 (i.e., 54 farmers from each district) were interviewed about their goat production systems and trait preferences to be improved. The chi-square test was used to analyze qualitative data, and analysis of variance was used to analyze quantitative data generated by the survey. For the rank data, indexes were calculated using Microsoft Excel 2010. Income was the main objective of goat rearing in all the study areas. Doe has a larger proportion than other flock structures in all the study areas. Mostly, the age of castration was above one year in all the study areas. The breeding buck selection criteria were growth, shape, size, and color. Body size, litter size, and mothering ability were identified as important traits in all study areas. Early selling of fast-buck kids is practiced in all study areas for their immediate cash. This results in the use of poor-performing bucks for breeding and may result in negative selection. To address such issues, it is critical to create and implement a community-based breeding program that takes into account body size, litter size, mothering capacity, puberty age, and longevity.